John Evelyn: Elysium Britannicum, or The Royal Gardens - Jaine, Tom (Petits Propos Culinaires, 2024)
John Evelyn: Elysium Britannicum, or The Royal Gardens: edited by John E. Ingram: University of Pennsylvania Press, Philadelphia, 2001: ISBN 0-8122-3536-3: 490 pp., b/w illus., h/b, £60.50.